If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 82 + -2x = 16x + 22 Reorder the terms: 82 + -2x = 22 + 16x Solving 82 + -2x = 22 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 82 + -2x + -16x = 22 + 16x + -16x Combine like terms: -2x + -16x = -18x 82 + -18x = 22 + 16x + -16x Combine like terms: 16x + -16x = 0 82 + -18x = 22 + 0 82 + -18x = 22 Add '-82' to each side of the equation. 82 + -82 + -18x = 22 + -82 Combine like terms: 82 + -82 = 0 0 + -18x = 22 + -82 -18x = 22 + -82 Combine like terms: 22 + -82 = -60 -18x = -60 Divide each side by '-18'. x = 3.333333333 Simplifying x = 3.333333333
| 8k^2-19k+9= | | 3(6x-7)+2x=14 | | a^2=15a | | -55-6x+12x=41 | | x+2y=20 | | -4+19=5b-3-4b | | 698=2(w+23) | | -5/2(w-1)=15 | | 3(j+5)=8(y+6) | | 4x-18=26 | | 14=6x+7y | | x^2-2x-3= | | 86=2(w+3) | | 6p^2+5p-6= | | 3/4(n+3)=9 | | -2p+6+3p=12 | | 10x-13=127 | | 6p^2-3p=0 | | x-2=x-5-x-2 | | 8+3x=44 | | -2+6+3p=12 | | 1/3(d+9)=-12 | | 3b-2-7b=26 | | 2h-1=23 | | 5x-11=36 | | -32-2x=8-10x | | x*2-8x=0 | | -4x+10=(-9) | | 0.03(m+7)=0.02(5-M)+0.03 | | 2n+6=20 | | 6w-2=16 | | -4x+10=9 |